MICROBIAL EVALUATION OF TIGER NUTS (Cyperus esculentus L.) SOLD IN ABA, ABIA STATE, NIGERIA. - C. C., Ike,; Ike, Emeka-; E. E., Akortha, (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2017)
The microbial evaluation of tiger nuts (Cyperus esculentus L.) sold in Aba metropolis was done using standard microbiological methods. A total of 20 samples drawn randomly from four (4) different traffic-prone areas in Aba metropolis were assessed. Mean aerobic bacterial, coliform and fungal counts (CFU/g) ranged between (4.5×103) ±0.55 to (3.3×104) ±0.31; (1.9×101) ±0.03 to (2.1×102) ±0.39 and (0.4×102) ±0.07 to (2.3×103) ±0.10 respectively. A total of seven bacterial and four fungal isolates were identified to include -bacteria: Bacillus species (40%), Pseudomonas species (28%), Staphylococcus species (23%), Proteus species (19%), Escherichia coli (7%), Klebsiella species (6%), Streptococcus species (5%) and fungi: Aspergillus species (25%) Penicillium species (21%), Rhizopus species (15%), Mucor species (11%). The high microbial counts reported in this work which are above acceptable thresholds are indications of serious health concern since the tubers are usually consumed without further washing. From the results obtained, it is advisable that an adequate campaign should be organized for the major stakeholders (vendors/ hawkers and consumers) in order to educate them on the inherent risks associated with the crude practices and applicable way forwards to avert food safety issues.